2018
DOI: 10.1074/jbc.ra118.004769
|View full text |Cite
|
Sign up to set email alerts
|

A DNA nick at Ku-blocked double-strand break ends serves as an entry site for exonuclease 1 (Exo1) or Sgs1–Dna2 in long-range DNA end resection

Abstract: The repair of DNA double-strand breaks (DSBs) by homologous recombination (HR) is initiated by nucleolytic resection of the DNA break ends. The current model, being based primarily on genetic analyses in and companion biochemical reconstitution studies, posits that end resection proceeds in two distinct stages. Specifically, the initiation of resection is mediated by the nuclease activity of the Mre11-Rad50-Xrs2 (MRX) complex in conjunction with its cofactor Sae2, and long-range resection is carried out by exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…In aggregate, our results suggest that individual loss of Exo1 or Sgs1 modestly reduces the accumulation of hairpin-mediated GCRs in sae2Δ mutants, consistent with a requirement for resection to expose stable hairpin-forming ssDNA sequences and the redundancy of the two pathways in resecting DNA at DSBs, DNA nicks, DNA gaps, and forked DNA structures (Thangavel et al, 2015;Wang et al, 2018). In addition, our data suggest that Yku70-Yku80 also suppresses the accumulation of short-loop ssDNA hairpins independently of Sae2, as demonstrated by the accumulation of short-hairpin foldback inversion GCRs in the yku80Δ single mutant and the exo1Δ yku80Δ and sgs1Δ yku80Δ double mutants, and the increased foldback inversion GCR rate in the sae2Δ yku80Δ double mutant.…”
Section: Efficient Dna Resection Promotes Foldback Inversion Formationsupporting
confidence: 76%
“…In aggregate, our results suggest that individual loss of Exo1 or Sgs1 modestly reduces the accumulation of hairpin-mediated GCRs in sae2Δ mutants, consistent with a requirement for resection to expose stable hairpin-forming ssDNA sequences and the redundancy of the two pathways in resecting DNA at DSBs, DNA nicks, DNA gaps, and forked DNA structures (Thangavel et al, 2015;Wang et al, 2018). In addition, our data suggest that Yku70-Yku80 also suppresses the accumulation of short-loop ssDNA hairpins independently of Sae2, as demonstrated by the accumulation of short-hairpin foldback inversion GCRs in the yku80Δ single mutant and the exo1Δ yku80Δ and sgs1Δ yku80Δ double mutants, and the increased foldback inversion GCR rate in the sae2Δ yku80Δ double mutant.…”
Section: Efficient Dna Resection Promotes Foldback Inversion Formationsupporting
confidence: 76%
“…Previous in vitro analysis of Mre11 activity on Ku-occluded dsDNA substrates revealed incisions at 35-45 and 55-65 bp from the end on 70 and 100 bp substrates, respectively (22,41), leading to the prevailing model wherein Mre11 creates a nick at a distance enforced by the Ku protein block (23). We observed a pattern of iterative peaks throughout this region consistent with the model and with the inference of a "stepwise" cleavage at somewhat regularly spaced positions Models cited above imply that Ku and/or Mre11 protein sizes are critical factors (22,23,41), but the pattern could be enforced by other proteins bound prior to damage such as histones or other proteins (42,43) and DNA repair proteins are can have sequence-specific properties (44,45). We addressed these issues using 3 bp deletions in the ILV1-PR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Also, separation of function Ku mutants have been isolated in yeast that are NHEJ proficient but show defective telomeres protection and reduced block of EXO1 resection in vitro ( 21 ). Second, reconstitution systems with purified proteins have shown that the Sae2 (budding yeast ortholog of CtIP) or CtIP-dependent endonucleolytic cleavage mediated by MRE11 of one DNA strand is stimulated near Ku- or Ku/DNA-PKcs-blocked DNA ends ( 26 , 27 , 74 ), providing an entry site for exonucleases responsible for long-range resection ( 28 ). Third, DNA-PKcs activated at seDSBs phosphorylates RPA2 ( 30 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%